TRANSFORMASI PEMIKIRAN PENDIDIKAN KH. AHMAD DAHLAN DI ERA DIGITAL: PERSPEKTIF PENDIDIKAN ISLAM MODERN - Arafah, Man (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article analyzes the transformation of KH. Ahmad Dahlan's educational thought in the digital era from the perspective of modern Islamic education. KH. Ahmad Dahlan emphasized that religious education and general scientific knowledge must be integrated in order to address the challenges of the times. This study employs a descriptive qualitative method, involving literature review, conceptual analysis, and case studies. The findings indicate that KH. Ahmad Dahlan’s educational ideas remain relevant in the modern era, particularly in developing an inclusive Islamic education that is adaptive to technological advancements